Understanding news-related user comments and their effects: a systematic review - Kubin, Emily; Merz, Pascal; Wahba, Mariam; Davis, Cate; Gray, Kurt; von Sikorski, Christian (Frontiers in Communication, 2024)
There has been growing interest in research on news-related user comments. Here we conduct the first systematic review of this literature¾quantitatively and qualitatively (248 studies)¾that covers the entire communication process (content analyses, surveys, experiments).Results indicate a focus on online news articles (vs videos) and little consideration for major social media platforms (Instagram, TikTok). Research often assess incivility in comments but offers conflicting conclusions on the actual level of incivility in comment threads-and seldom considers how to effectively combat any incivility. We propose four priorities for future work: more comparative and longitudinal approaches; exploring social media and video content; examining platform design, content moderation and artificial intelligence; and implementing measures to reduce incivility and protect the integrity of journalism.